Faktor-Faktor yang Memengaruhi Keuntungan UMKM Handicraft Berbahan Kayu di Kabupaten Jepara - Aminah, Ines Fitriana; Ferichani, Minar; Riptanti, Erlyna Wida (Jurnal E-Bis, 2025)
MSMEs in Indonesia continue to grow and support the economy, including in Jepara Regency. MSMEs making wooden handicrafts have begun to develop amidst the sluggish furniture industry due to tight competition. This study aims to analyze the factors that influence the profits of MSMEs making wooden handicrafts in Jepara Regency. Using a descriptive quantitative approach method with purposive and snowball sampling techniques for 30 respondents. Observation, interviews, and documentation are data collection techniques. Data analysis uses multiple linear regression with classical assumption tests and hypothesis tests. The results show that selling price, sales volume, raw material costs, labor costs, length of business, and online marketing simultaneously affect profits. Individually, each independent variable has a positive and significant effect on profits. MSME actors are advised to implement a value-based pricing, optimize offline and online marketing, utilize wood waste, increase workforce productivity through training, and make promotions more effective to attract consumers.